Robert Sterry correspondence - Sterry, Robert
ALS (Philadelphia) from Sterry to John Boileau pertaining to Gen. Joseph Bloomfield's orders for the requisition of militia during the War of 1812.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bloomfield, Joseph, -- 1753-1823.; Boileau, John -- Correspondence; Militia; United States -- History -- War of 1812.; Army officers